Inglês na abordagem instrumental: estratégias de ensino no contexto da educação profissional e tecnológica - Cardoso, Eliete Silva (2023)
This study integrates research line 1: "Educational Practices in Professional and Technological Education" and macroproject 3: Educational Practices in the Integrated Curriculum, of the Professional Master's Degree in Professional and Technological Education (ProfEPT), Associated Institution of the Federal Institute of Amazonas - IFAM. The general objective was to analyze the teachers' difficulties in applying the teaching of English to the High School Courses Integrated to Professional and Technological Education of the Federal Institute of Education, Science and Technology of Pará (IFPA) - Campus Itaituba. From the results, an educational product was elaborated to help the teacher, aiming at an integral and omnilateral human formation. The study is justified by the fact that the researcher is one of the professors of the English teaching staff, in these courses, and has experienced the problem of lack of didactic materials in English classes. Teachers of English and students of High School Integrated to Vocational and Technological Education (EPT) were involved in the research. To achieve this goal, the articulation of the concepts of Integral and Omnilateral Human Formation and Instrumental English Teaching and the data construction method were observed with a theoretical study on the current situation of English teaching in these courses, with a Literary Review of works and articles published in educational research, identifying in the National Common Curricular Base (BNCC), the skills and abilities developed by high school students, contributing so that the teaching of instrumental English makes a difference in the human formation of the student and in the world of work. Based on Gil (2002), a survey was carried out of the teachers' difficulties in teaching English at this level of schooling and introducing the new Digital Information Technologies. Interviews and questionnaires guided the research, with 3 English teachers and 25 students of the 3 rd grade of the Buildings Course (8) and Information Technology (17), totaling 28 participants. Descriptions and quantitative and qualitative analyzes of the data were carried out through action research. According to Yin (2017, p.15), the exploratory and explanatory research is conceived from the perspective of the participants, resulting in an Educational Product “Podcast Instrumental English” for teachers and students as a teaching strategy. It is concluded that English in the instrumental approach contributes to motivate students and teachers to use new codes and digital media for teaching and learning a foreign language.